Regional'nyi komponent v muzykal'nom obrazovanii shkol'nikov - Zarubina O. A., Mikhailov S. A. (Pedagogical innovations: from theory to practice)
The inclusion of a regional component in the education system allows pupils to introduce the younger generation to the roots of their homeland, discover her story, to establish a connection with modernity. The article reveals the necessity of studying the lessons of music in school the musical heritage of his native land, which affects the attitude of the student to his school, to his family, to its unique culture and is an indispensable condition of Patriotic education.
Keywords: патриотическое воспитание; малая родина; музыкальное образование; национальная культура; региональный компонент; музыкальная культура; patriotic education; national culture; musical education; musical culture; small homeland; the regional component